Validation of Empirical Formulas for Spallation Residue Production in 0.3A-1.5A GeV 56Fe+p Reactions - Nicolis, Nikolaos George; Katsigianni, Theodora-Ilektra; Korakas, Kostantinos; Miliadou, Athanasia; Tasioudis, Diamantis (HNPS Advances in Nuclear Physics, 2022)
The production of spallation residues in 56Fe+p bombardments is described with empirical parametric formulas often used in cosmic-ray astrophysics, activation studies and isotope production for medical applications. Experimental observables including mass, charge and isotopic distributions are compared with calculations using two versions of the formulas of Rudstam and Silberberg-Tsao and the SPACS formula. For reference, a comparison is made with the predictions of a two-stage reaction model. Deviation factors obtained in these approaches are reported.